LINGUO-PRAGMATIC FEATURES OF TRANSLATIONS OF ANTHROPONYMS IN THE TEXT OF “BABURNOMA” (Scientific journal of the Fergana State University, 2023)
This article is devoted to the translation of anthroponyms in the text “Baburnoma” by using transliteration, word for word translation, calque, and figurative expression, as well as the problems and solutions in it. The analysis of the translations shows that the classification of anthroponyms in the text of “Baburnoma” is also simple, clear, and laconic.